2022
DOI: 10.1038/s41598-022-13540-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of socioeconomic and parental involvement factors on children foundational learning skills based on MICS (2017–2018) data Punjab, Pakistan

Abstract: Developing countries lack studies investigated the socioeconomic and parental role on students’ learning skills. This study is helpful to detect bottlenecks in the foundational learning skills (reading skills and numeracy skills) in the education system of Pakistan. Reading skills of children are found better who had no functional disabilities. Mothers with higher education had a significant positive contribution toward children learning skills. Children deprived of books for reading in appropriate language ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Naite (2021) affirms that parents' education level, age, employment and marital status had a great impact on their children's education. According to Kamal et al (2022) the wealth index has been used as a proxy for the source of income status in previous studies and has been found to be a significant predictor of children's learning outcomes in terms of literacy and numeracy skills.…”
Section: Parental Factors Determining Children's Competences In Liter...mentioning
confidence: 99%
“…Naite (2021) affirms that parents' education level, age, employment and marital status had a great impact on their children's education. According to Kamal et al (2022) the wealth index has been used as a proxy for the source of income status in previous studies and has been found to be a significant predictor of children's learning outcomes in terms of literacy and numeracy skills.…”
Section: Parental Factors Determining Children's Competences In Liter...mentioning
confidence: 99%